Diagnosis and Management of Beckwith-Wiedemann Syndrome - Wang, Kathleen H.; Kupa, Jonida; Duffy, Kelly A.; Kalish, Jennifer M. (Frontiers in Pediatrics, 2020)
Beckwith-Wiedemann syndrome (BWS) is a human genomic imprinting disorder that presents with a wide spectrum of clinical features including overgrowth, abdominal wall defects, macroglossia, neonatal hypoglycemia, and predisposition to embryonal tumors. It is associated with genetic and epigenetic changes on the chromosome 11p15 region, which includes two imprinting control regions. Here we review strategies for diagnosing and managing BWS and delineate commonly used genetic tests to establish a molecular diagnosis of BWS. Recommended first-line testing assesses DNA methylation and copy number variation of the BWS region. Tissue mosaicism can occur in patients with BWS, posing a challenge for genetic testing, and a negative test result does not exclude a diagnosis of BWS. Further testing should analyze additional tissue samples or employ techniques with higher diagnostic yield. Identifying the BWS molecular subtype is valuable for coordinating patient care because of the (epi)genotype-phenotype correlations, including different risks and types of embryonal tumors.